2021
DOI: 10.1111/1460-6984.12670
|View full text |Cite
|
Sign up to set email alerts
|

Does a simulation‐based learning programme assist with the development of speech–language pathology students’ clinical skills in stuttering management?

Abstract: Background: Simulation-based learning can be used in university programmes to provide speech-language pathology students with essential clinical experiences. However, limited research has explored the use of simulation to support students' development of skills in clinical practice with people who stutter. Aims: (1) To evaluate students' clinical skills in managing stuttering within a simulation-based learning programme; (2) to develop an assessment tool, the Standardised Patient Interview Rating Scale for Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Investigation of students' insights into and development of clinical skills in an in-person stuttering SBL revealed that students demonstrated an improvement in the management of stuttering (Penman et al, 2021). The present study suggests that similar positive outcomes are also achievable when the SBL experience is converted to an online modality.…”
Section: Discussionsupporting
confidence: 55%
“…Investigation of students' insights into and development of clinical skills in an in-person stuttering SBL revealed that students demonstrated an improvement in the management of stuttering (Penman et al, 2021). The present study suggests that similar positive outcomes are also achievable when the SBL experience is converted to an online modality.…”
Section: Discussionsupporting
confidence: 55%
“…In some simulation programmes, there are timetabled slots to give individual one‐to‐one feedback. There is evidence to suggest in specific contexts that personalized feedback from the facilitator can aid the student's learning (Penman et al., 2021). This was not included in this simulation programme due to time constraints.…”
Section: Discussionmentioning
confidence: 99%